Letter : Spanish seamen - Chandley, A. J.
025a-0024-001 Telegraphic Address TRADESUNION SOWEST LONDON Telephone Victoria 7671/5 Transport and General Workers' Union Registered Trade Union No. 18341. Approved Society for National Health Insurance No. 398 Registered Offices Transport House, Smith Square Westminster, London, S.W.1. General Secretary Ernest Bevin Financial Secretary Stanley Hirst Asst General Secretary Arthur Deakin AJC/BG Mr. H.V.Tewson, 28th October 1940. Trades Union Congress, Transport House, Dear Mr.Tewson, SPANISH SEAMEN I have had a word with Mr. Deakin arising out of our brief conversation last week and have explained the position in regard to the above as you put it to me. However, he is clearly of the opinion that it as purely a question of releasing our proportion of the original grant. Therefore, if a further grant is to be made, I can only suggest that you write to Mr. Deakin again and then I have no doubt that he will arrange to have the matter brought before our Executive Council when they are next in session during the week of November 11th. Yours sincerely, A.J. Chandley Chief Clerk 292/946/25a/24